The Theory of Planned Behavior to Identify Out-of-Hospital Cardiac Arrest (OHCA) Bystanders' Intentions - Zenita Habibatul Ilmiyah; Sri Andarini; Tony Suharsono (Jurnal Kedokteran Brawijaya, 2022)
The theory of planned behavior states that intention is the best predictor of behavior. The intention to perform a behavior is determined by a person's attitude, subjective norms, and perceived behavioral control. As volunteers in the health sector, volunteers of the Indonesian Red Cross (PMI) have been equipped with knowledge and skills regarding the role of an OHCA bystander. Besides, the intentions of PMI volunteers greatly affect a person's tendency to be willing or unwilling to become an OHCA bystander. This study aims to apply the theory of planned behavior in identifying the factors that influence the intentions of PMI volunteers in acting as OHCA bystanders and the dominant factors that affect intentions. This study used an observational research type with a cross-sectional approach. The respondents in this study were 105 PMI volunteer members in Tuban Regency, which were conducted using the purposive sampling technique. In determining the most dominant factor that influenced intention, ordinal logistic regression analysis was used in which it was shown that the variable used in the last modeling analysis stage was the subjective norm (OR= 6.19). Based on the results of the analysis, it can be concluded that subjective norms are the most predictor factor that influences intentions.